Atypical carcinoma detected after regression of a ``benign'' oral white lesion. A case report - Srubar, Jan; Uhrikova, Tereza; Delongova, Patricie (Biomedical papers, 2021)
Background. Unlike leukoplakia, the smokers' lesion - a type of oral white lesion spontaneously regressing following cessation of smoking - is generally considered a non-serious condition and there is no recommendation for subsequent follow-up of such patients. Case report. Here, however, we present the case of a patient (female, 56, smoker) in whom we detected a smoker's lesion which regressed completely, without any signs of abnormality or malignity. The only shadow of a doubt that led us to inviting her for another examination was an additional examination using a VELscope(R) autofluorescence device that revealed autofluorescence suppression on the site of the former lesion. Another examination one month later revealed a patch of epithelium with a normal color but a negligibly different light reflection in the center of the former lesion; VELscope(R) indicated the questionable area to still be suspect. Following excision using margins indicated by VELscope(R) (+2-3 mm), histopathology revealed a squamous cell carcinoma. The secondary excision was carcinoma free and even after 5 years, the carcinoma has not recurred. Conclusion. We would like to point out that apparent spontaneous regressions of oral white lesions following smoking cessation still need attention and close follow-up to make sure that a developing squamous cell carcinoma cannot pass undetected.
Keywords: smokers' lesion; oral white lesion; squamous cell carcinoma; leukoplakia; regression; cessation of smoking